China and SAARC: Connectivity —— Need for an Enabling Environment. (1st January 2014) - ,
Abstract : Connectivity with others is among the basic requirements of human beings, societies and nations. It has been present, and continues to expand, in form and substance. Things are being shaped up quite rapidly with the advancement in information and communication technologies. In the particular context of China and South Asian countries, while physical connectivity and the development of related infrastructure —— roads and railways, bridges, pipelines, and communication lines etc. —— remain the important element in improving the relationship, more vital is to focus on soft i.e. non-physical aspects of connectivity; policies, procedures and rules. Thus, a favorable regulatory mechanism with regard to the movement of people, goods, finances as well as information is required. On a greater level, mental, political and social connectivity between the people, is a prerequisite. This, in turn, would provide a lasting and sustainable foundation for good relations. Revised version of the Paper presented in the China-South Asia Think-Tank Forum held in Kunming, China, on June 6––7, 2013, under the auspices of Institute of South Asian Studies, Yunnan Academy of Social Sciences.